ANALISIS POTENSI EKONOMI SEKTORAL KABUPATEN HUMBANG HASUNDUTAN TAHUN 2010-2018 - Elvis F. Purba (Visi Sosial Humaniora, 2020)
This paper describes the economic potential of each industrial origin Humbang Hasundutan regency period 2010-2018. The analysis is based on: (1) location quotient (LQ), (2) sectoral contribution to GDRP, and (3) sectoral contribution to the regency's economic growth rate. Assuming that there is no a drastic change in the sectoral GDRP value in one or several industrial origin, the annual average value from the observation period is used. Furthermore, to determine the economic potential of each industrial origin based on established quantitative criteria. The results of data analysis indicate that only one industrial origin has high economic potential, namely agriculture, forestry and fisheries. Then there are two industrial origin with moderate potential, i.e.: (1) construction and (2) government administration, defense and campulsory social security. The remaining fourteen other industrial origin have low potential. Over time, it is estimated that there will be changes in the contribution of each industrial origin to GDRP and the rate of regency economic growth. However, agriculture, forestry and fisheries are estimated to still have high potential in the next few decades, especially since Humbang Hasundutan regency has been designated as one of the food estate for Indonesia.